How Well Does the Family Longevity Selection Score Work: A Validation Test Using the Utah Population Database - Arbeeva, Liubov S.; Hanson, Heidi A.; Arbeev, Konstantin G.; Kulminski, Alexander M.; Stallard, Eric; Ukraintseva, Svetlana V.; Wu, Deqing; Boudreau, Robert M.; Province, Michael A.; Smith, Ken R.; Yashin, Anatoliy I. (Frontiers in Public Health, 2018)
The Family Longevity Selection Score (FLoSS) was used to select families for the Long Life Family Study (LLFS) but has never been validated in other populations. The goal of this paper is to validate how well the FLoSS-based selection procedure works in an independent dataset. In this paper, we computed FLoSS using the lifespan data of 234,155 individuals from a large comprehensive genealogically-based resource, the Utah Population Database (UPDB), born between 1779 and 1910 with mortality follow-up through 2012-2013. Computations of FLoSS in a specific year (1980) confirmed the survival advantage of the “exceptional” sibships (defined by LLFS FLoSS threshold, FLoSS>=7). We found that the subsample of the UPDB participants born after 1900 who were from the “exceptional” sibships had survival curves similar to that of the US participants from the LLFS probands’ generation. Comparisons between the offspring of parents with “exceptional” and “ordinary” survival showed the survival advantage of the “exceptional” offspring. Investigators seeking to explain the extent genetics and environment contribute to exceptional survival will benefit from the use of exceptionally long-lived individuals and their relatives. Appropriate ranking of families by survival exceptionality and their availability for the purposes of providing genetic and phenotypic data is critical for selecting participants into such studies. This study validated the FLoSS as selection criteria in family longevity studies using UPDB.